Transvesical Prostate Adenomectomy in Mbujimayi: Frequency, Clinical Presentation, and Postoperative Outcomes. - Banema, Edmond Issa Kanda; Kabamba, Trésor Kabuya; Katulondi, Séraphin Binene; Kabila, Joseph Luboya; Tangila, Pierre Tangila; Makubakuba, Delphin Kayembe; Yombo, Alidor Mbangila; Mutombo, Clément Kadima; Nkumu, Matthieu Loposso; Akinja, Séverin Uwonda; et al. (International Journal of Health Sciences, 2026)
Purpose: Transvesical prostate adenomectomy remains a relevant option in low-resource settings despite the growing availability of minimally invasive techniques. This study aimed to assess the current practice of this procedure in Mbujimayi. Methods: This descriptive, retrospective, multicenter study included 85 patients who underwent transvesical prostate adenomectomy between January 1, 2019, and December 31, 2024. Results: The frequency of transvesical prostate adenomectomy was 15.2%. The mean age of the patients was 69.5± 7.1years. Most patients presented late, often after resorting to traditional treatment (69.8%), and chronic urinary retention was the main reason for consultation (56.5%). A three-way transurethral catheter alone was the most commonly used intraoperative device. The mean operative time was 69.1 ± 20.7minutes, and all patients received transfusions. Early postoperative complications were frequent (50.6%); mainly deep surgical site infections associated with vesicocutaneous fistulas (30.2%). The mean postoperative stay was 20.2 ± 12.4 days. The outcome was favorable in 96.5% of cases, and the mortality rate was 3.5%. Conclusion: Transvesical prostatectomy is commonly performed in our setting, particularly in elderly patients who present late with chronic urinary retention. Despite the high rate of postoperative morbidity, the overall outcome remains satisfactory. Unique contribution to theory, practice and health policy: This study provides the first local data on transvesical prostate adenomectomy and offers key insights to improve perioperative care and guide health policy in resource‑limited settings such as Mbujimayi.